Enhanced Mutation Rate, Relaxed Selection, and the "Domino Effect" are associated with Gene Loss in Blattabacterium, A Cockroach Endosymbiont. (26th May 2021) - Kinjo, Yukihiro; Lo, Nathan; Martín, Paula Villa; Tokuda, Gaku; Pigolotti, Simone; Bourguignon, Thomas
Abstract: Intracellular endosymbionts have reduced genomes that progressively lose genes at a timescale of tens of million years. We previously reported that gene loss rate is linked to mutation rate in Blattabacterium, however, the mechanisms causing gene loss are not yet fully understood. Here, we carried out comparative genomic analyses on the complete genome sequences of a representative set of 67 Blattabacterium strains, with sizes ranging between 511 and 645 kb. We found that 200 of the 566 analyzed protein-coding genes were lost in at least one lineage of Blattabacterium, with the most extreme case being one gene that was lost independently in 24 lineages. We found evidence for three mechanisms influencing gene loss in Blattabacterium . First, gene loss rates were found to increase exponentially with the accumulation of substitutions. Second, genes involved in vitamin and amino acid metabolism experienced relaxed selection in Cryptocercus and Mastotermes, possibly triggered by their vertically inherited gut symbionts. Third, we found evidence of epistatic interactions among genes leading to a "domino effect" of gene loss within pathways. Our results highlight the complexity of the process of genome erosion in an endosymbiont.